1995
DOI: 10.1111/j.1432-2277.1995.tb01498.x
|View full text |Cite
|
Sign up to set email alerts
|

Human herpesvirus-6 infection in renal allografts: retrospective immunohistochemical study in Japanese recipients

Abstract: This study was conducted to determine the incidence and clinical significance of human herpesvirus-6 (HHV-6) infection in renal allografts. A total of 105 biopsy specimens from 72 recipients were immunohistochemically examined for the presence of HHV-6 antigen, which localized in the distal tubular epithelial cells and in a few lymphocytes infiltrating into the interstitium. HHV-6 antigen in the tubular epithelia was detected in 63 (61.2%) specimens. Categorically, a higher incidence of the antigen was noted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
(14 reference statements)
3
24
0
2
Order By: Relevance
“…The role of HHV-6 infection in allograft rejection has been examined in renal transplant recipients. Helanterä et al (7) and Hoshino et al (8) showed that HHV-6 antigen was expressed in tubular cells in renal transplant recipients, but they described no clear association of HHV-6 infection with renal dysfunction. On the other hand, some researchers have suggested that reactivation of HHV-6 may induce rejection of renal transplants (9).…”
Section: Discussionmentioning
confidence: 99%
“…The role of HHV-6 infection in allograft rejection has been examined in renal transplant recipients. Helanterä et al (7) and Hoshino et al (8) showed that HHV-6 antigen was expressed in tubular cells in renal transplant recipients, but they described no clear association of HHV-6 infection with renal dysfunction. On the other hand, some researchers have suggested that reactivation of HHV-6 may induce rejection of renal transplants (9).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical manifestations of HHV-6 reactivation or reinfection in SOT recipients are similar to those described in BMT patients. These include fever and/or rash as the most frequently seen disease manifestation of active HHV-6 infection (150,363,384,449,451), followed by encephalitis or encephalopathy (291,323,363,384), hepatitis (150,384,427), graft dysfunction or rejection (2,15,168,231), bone marrow suppression (362,363), and pneumonitis (362). Table 2 provides a summary of prospective studies in SOT patients.…”
Section: Clinical Manifestations Of Hhv-6 Infectionmentioning
confidence: 99%
“…Qualitative or quantitative HHV‐6 PCR of the cerebrospinal fluid is useful to diagnose HHV‐6 encephalitis in patients with the appropriate clinical signs . Immunohistochemistry to detect viral antigens in biopsy specimens may be more informative than viremia in cases where tissue‐invasive HHV‐6 disease is suspected . However, HHV‐6 antigen may be found commonly in tissue in the absence of symptoms .…”
Section: Human Herpesviruses 6 Andmentioning
confidence: 99%